Learning Quantum Chemical Model with Learning Media Concept Map and Power Point Viewed from Memory and Creativity Skills Students - Agus Wahidi (STKIP Singkawang, 2017)
This research is experimental, using first class learning a quantum model of learning with concept maps media and the second media using real environments by power point presentation. The population is all class XI Science, number 2 grade. The sampling technique is done by purposive random sampling. Data collection techniques to test for cognitive performance and memory capabilities, with a questionnaire for creativity. Hypothesis testing using three-way ANOVA different cells with the help of software Minitab 15.Based on the results of data processing, concluded: (1) there is no influence of the quantum model of learning with media learning concept maps and real environments for learning achievement chemistry, (2) there is a high impact memory ability and low on student achievement, (3) there is no the effect of high and low creativity in student performance, (4) there is no interaction learning model quantum media learning concept maps and real environments with memory ability on student achievement, (5) there is no interaction learning model quantum media learning concept maps and real environments with creativity of student achievement, (6) there is no interaction memory skills and creativity of student achievement, (7) there is no interaction learning model quantum media learning concept maps and real environments, memory skills, and creativity on student achievement.